Formulation And Evaluation Of The Preparation Of Hard Candy Source Of Sweet Orange (Citrus Sinensis (L.) Osbeck) As A Nutracetical - Mauliza, Syarifah; Indrayani Dalimunthe, Gabena (Publisher Cv. Inara, 2022)
Candy is used as a source of high calories, so it is often eaten during activities such as work, studying, and exercise. In general, the candy that is widely circulated in the community is hard candy, which has a hard texture and a shiny appearance. The benefits of candy for the human body are that it adds nutrients, minerals, and other vitamin content because this candy is made from real fruit juice. The purpose of this study was to formulate hard candy with the main ingredient of sweet orange juice with a variety of sucrose in order to get a delicious formula in the form of taste that is expected to meet the nutritional requirements of both children and adults. formulated candy. Hard candy is made using the open pan method. The research is experimental and includes the processing of sweet orange ingredients, making sweet orange juice, making hard candy and hard candy test parameters including organoleptic tests, pH tests, weight uniformity tests, water content tests, ash content tests and tests of preference level (hedonic test) by the respondent. Based on the results of the study, sweet orange juice can be formulated into hard candy preparations with sucrose 1,5; 2 and 3 g. The obtained results with candy shape, taste, and hardness are quite good; they have a pH of 5, and they meet weight uniformity requirements with a coefficient of variation of 1.08, 1.30, and 1.11%, moisture content 2.4, 2.3 and 1.7%, ash content 1.0, 0.13 and 0%. The results of the organoleptic preference level test in terms of liking, taste, and texture showed that F3 was the most preferred formula. The sucrose levels have an effect on the level of liking.